A Case Study of the Impact of Implementing Activity Based Costing and Target Costing on Increasing Profit at PT Fajar Surya Wisesa Tbk in the 2018-2021 Period - Giselawati, Dinda; Iryani, Lia Dahlia; Rahmi, Amelia (Journal of Islamic Contemporary Accounting and Business, 2024)
The purpose of this research is to analyze the implementation of Activity Based Costing and Target Costing in increasing profits at PT Fajar Surya Wisesa Tbk. The data used in this study is secondary data. The indicators used for Activity Based Costing are determined by setting the rate of Factory Overhead Cost (FOC) per activity group. For Target Costing indicators, it involves calculating the selling price minus the targeted profit. The profit variable indicator involves detailing sales based on the cost of production. The results of this study show that the use of Activity Based Costing method has an impact on cost calculations that focus on production costs, with an increase in the Cost of Goods Manufactured (COGM) before the application of Activity Based Costing. This results in an increase in the cost of goods manufactured, leading to a decrease in company profits. On the other hand, the implementation of Target Costing proves that Target Costing is an alternative effort to maximize the targeted profit by the company.